2016
DOI: 10.1002/adma.201505113
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic 3D CMOS Using Layered Semiconductors

Abstract: Monolithic 3D integrated circuits using transition metal dichalcogenide materials and low-temperature processing are reported. A variety of digital and analog circuits are implemented on two sequentially integrated layers of devices. Inverter circuit operation at an ultralow supply voltage of 150 mV is achieved, paving the way to high-density, ultralow-voltage, and ultralow-power applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
97
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 24 publications
0
97
0
2
Order By: Relevance
“…Some of ultra-thin CMOS inverters reported in the literature are summarized in Table VI. 186,[188][189][190][191] Only few of them have investigated the effect of bending stress on the performance. The performance of the thinned Si CMOS inverter circuit by Kino et al 191 degrades under bending stress, as shown in Fig.…”
Section: Invertersmentioning
confidence: 99%
“…Some of ultra-thin CMOS inverters reported in the literature are summarized in Table VI. 186,[188][189][190][191] Only few of them have investigated the effect of bending stress on the performance. The performance of the thinned Si CMOS inverter circuit by Kino et al 191 degrades under bending stress, as shown in Fig.…”
Section: Invertersmentioning
confidence: 99%
“…[1][2][3][4][5] An intrinsic difference of monolayer TMDCs from graphene is the direct bandgap (such as the MoS 2 monolayer with a bandgap of about 1.9 eV (ref. 6 and 7)), which enables these materials to have potential applications not only in eld-effect transistors (FETs), [8][9][10][11] but also in future optoelectronics (such as photodetectors and phototransistors).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Strain-induced Self-Rolled-up Membranes (S-RuM) are of great interest due to their CMOS-compatible planar fabrication process and versatile 3D architectures produced by selfassembly. [1][2][3][4][5][6][7][8][9][10][11] Strain-induced Self-Rolled-up Membranes (S-RuM) are of great interest due to their CMOS-compatible planar fabrication process and versatile 3D architectures produced by selfassembly.…”
mentioning
confidence: 99%